Lithium manganese iron phosphate positive electrode material, preparation method thereof and lithium ion battery

By forming a highly conductive compound coating layer on the outer surface of the lithium manganese iron phosphate cathode material, the problems of manganese leaching and poor conductivity are solved, thereby improving the conductivity and cycle performance of the material.

CN119297241APending Publication Date: 2025-01-10SICHUAN TIANLI LITHIUM ENERGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411440133.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-15
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

Excessive manganese in lithium iron phosphate cathode materials leads to poor conductivity and manganese dissolution during charge and discharge, reducing cycle life.

Method used

A coating layer containing highly conductive compounds is formed on the outer surface of the lithium manganese iron phosphate cathode material. The highly conductive compounds include manganese and non-metallic elements such as B, S, P, Si, As, and Se. The coating layer may also contain carbon, and the thickness and composition ratio of the coating layer are controlled.

Benefits of technology

It improves the conductivity of lithium manganese iron phosphate cathode material, inhibits manganese dissolution, and improves cycle performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119297241A_ABST
    Figure CN119297241A_ABST
Patent Text Reader

Abstract

The invention provides a lithium manganese iron phosphate positive electrode material, a preparation method thereof and a lithium ion battery, and relates to the field of secondary batteries. The lithium manganese iron phosphate positive electrode material comprises an inner core and a coating layer located on the outer surface of the inner core, a material for forming the inner core comprises lithium manganese iron phosphate, a material for forming the coating layer comprises a high-conductivity compound, the high-conductivity compound comprises manganese and a non-metallic element, and the non-metallic element comprises any one of B, S, P, Si, As and Se. The coating layer containing the high-conductivity compound is formed on the outer surface of the lithium manganese iron phosphate, so that the resistivity of the material can be reduced, the dissolution of the manganese element in the lithium manganese iron phosphate can be inhibited, and the cycle performance of the material can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of secondary batteries, and in particular to a lithium iron manganese phosphate positive electrode material and a preparation method thereof and a lithium ion battery. Background Art

[0002] Lithium iron manganese phosphate (LiMnFePO4) is an emerging cathode material for lithium-ion batteries. It combines the advantages of lithium iron phosphate (LiFePO4) and lithium manganese phosphate (LiMnPO4), showing high energy density, good thermal stability and good cycle life, which has attracted widespread attention. In general, lithium iron manganese phosphate cathode materials improve the overall performance of batteries by combining the advantages of iron and manganese, making them have great application potential in electric vehicles and large-scale energy storage systems.

[0003] However, excessive addition of manganese in lithium manganese iron phosphate will lead to poor conductivity of the material, and the material will have the problem of manganese dissolution during the battery charging and discharging process, thereby significantly reducing the cycle life of lithium manganese iron phosphate. Therefore, it is necessary to improve the lithium manganese iron phosphate positive electrode material and its preparation method. Summary of the invention

[0004] The purpose of the present application is to provide a lithium iron manganese phosphate positive electrode material and a preparation method thereof and a lithium ion battery to solve the above problems.

[0005] To achieve the above objectives, this application adopts the following technical solutions:

[0006] The present application provides a lithium iron manganese phosphate positive electrode material, comprising: a core and a coating layer located on the outer surface of the core, the material forming the core comprises lithium iron manganese phosphate, the material forming the coating layer comprises a high-conductivity compound, the high-conductivity compound comprises manganese and a non-metallic element, and the non-metallic element comprises any one of B, S, P, Si, As, and Se.

[0007] According to an embodiment of the present application, the highly conductive compound accounts for 0.05-0.5wt% in the lithium iron manganese phosphate positive electrode material;

[0008] And / or, the coating layer further includes carbon, and the carbon in the coating layer accounts for 1.5-2.5wt% of the lithium manganese iron phosphate positive electrode material;

[0009] And / or, the coating layer has a thickness of 20-60 nm.

[0010] According to an embodiment of the present application, the molar amount of manganese in the lithium manganese iron phosphate accounts for more than 60% of the sum of the molar amounts of manganese and iron;

[0011] And / or, the material forming the inner core includes carbon, and the carbon in the inner core accounts for 0.1-0.5 wt % of the inner core.

[0012] The present application also provides a method for preparing the lithium manganese iron phosphate positive electrode material as described above, comprising:

[0013] A lithium source, a first manganese source, an iron source, a phosphorus source, a first reducing carbon source and water are mixed, and first spray drying and first sintering are performed in sequence to obtain a core material;

[0014] The core material, the second reducing carbon source, the non-metallic element, the second manganese source and water are mixed, and a second spray drying and a second sintering process are performed in sequence to obtain a lithium manganese iron phosphate positive electrode material;

[0015] Wherein, the non-metallic element includes any one of B, S, P, Si, As, and Se.

[0016] According to an embodiment of the present application, the lithium source includes a lithium salt or a hydrate of a lithium salt, and the lithium salt includes at least one of lithium carbonate, lithium phosphate, lithium dihydrogen phosphate, and lithium hydroxide;

[0017] And / or, the first manganese source includes at least one of trimanganese tetroxide, manganese dioxide, dimanganese trioxide, and manganese carbonate;

[0018] And / or, the iron source includes at least one of ferric phosphate, ferric oxalate, ferric oxide, and ferrosoferric oxide;

[0019] And / or, the phosphorus source includes at least one of lithium dihydrogen phosphate, iron phosphate, ammonium dihydrogen phosphate, and phosphoric acid;

[0020] and / or, the molar ratio of lithium in the lithium source to manganese in the first manganese source, iron in the iron source, and phosphorus in the phosphorus source is 1.05:(0.50-0.90):(0.10-0.50):(1.00-1.03);

[0021] and / or, the first reducing carbon source comprises glucose;

[0022] And / or, the content of the first reducing carbon source satisfies at least one of the following conditions: the ratio of the molar amount of the carbon element in the first reducing carbon source to the sum of the molar amounts of the trivalent metal elements in the first manganese source and the iron source is (1.02-1.1):4, and the ratio of the molar amount of the carbon element in the first reducing carbon source to the molar amount of the tetravalent manganese element in the first manganese source is (1.02-1.1):2;

[0023] And / or, before the first spray drying, the method further comprises a step of first grinding, and the D50 of the material after the first grinding is 0.18-0.22 μm;

[0024] And / or, the first sintering is performed under the protection of an inert gas, the temperature of the first sintering is 660-790° C., and the time of the first sintering is 8-14 hours.

[0025] According to an embodiment of the present application, the second reducing carbon source includes at least one of citric acid, ascorbic acid, tartaric acid, and gluconic acid;

[0026] And / or, the second manganese source includes at least one of manganese acetate, manganese citrate, manganese oxalate, and manganese tartrate.

[0027] According to an embodiment of the present application, the mass ratio of the core material to the second reducing carbon source is (17-20):1.

[0028] According to an embodiment of the present application, the molar ratio of the non-metallic element to the manganese in the second manganese source is (1-2):1;

[0029] And / or, the non-metallic element accounts for 0.015%-0.30% of the mass of the core material;

[0030] And / or, before the second spray drying, the method further comprises a second grinding step, and the D50 of the material after the second grinding is 0.20-0.40 μm.

[0031] According to an embodiment of the present application, after mixing the core material, the second reducing carbon source, the non-metallic element, the second manganese source, and water, the method further comprises the step of adjusting the pH of the slurry to 4.0-6.0;

[0032] And / or, the second sintering is performed under the protection of an inert gas, the temperature of the second sintering is 550-610° C., and the time of the second sintering is 4-8 hours.

[0033] The present application also provides a lithium-ion battery, which includes the lithium iron manganese phosphate positive electrode material described above or includes the lithium iron manganese phosphate positive electrode material prepared by the preparation method of the lithium iron manganese phosphate positive electrode material described above.

[0034] Compared with the prior art, the beneficial effects of this application include:

[0035] The present application forms a coating layer containing a highly conductive compound on the outer surface of the lithium manganese iron phosphate, which can reduce the resistivity of the material while inhibiting the dissolution of manganese elements in the lithium manganese iron phosphate and improving the cycle performance of the material. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope of the present application.

[0037] Figure 1 This is a SEM image of the lithium manganese iron phosphate positive electrode material prepared in Example 1;

[0038] Figure 2 TEM image of the lithium iron manganese phosphate positive electrode material prepared in Example 1;

[0039] Figure 3 This is the TEM image of the lithium manganese iron phosphate positive electrode material prepared in Comparative Example 3. DETAILED DESCRIPTION

[0040] As used herein:

[0041] "Prepared from" is synonymous with "comprising." As used herein, the terms "comprising," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.

[0042] The conjunction "consisting of excludes any unspecified element, step, or component. If used in a claim, this phrase renders the claim closed-ended so that it does not include materials other than those described, except for conventional impurities associated therewith. When the phrase "consisting of" appears in a clause of the body of a claim rather than immediately following the subject matter, it limits only the elements described in that clause; other elements are not excluded from the claim as a whole.

[0043] When an amount, concentration, or other value or parameter is expressed as a range, a preferred range, or a range defined by a series of upper preferred values ​​and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including ranges "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5", etc. When a numerical range is described in this article, unless otherwise stated, the range is intended to include its end values ​​and all integers and fractions within the range.

[0044] In these examples, parts and percentages are by mass unless otherwise indicated.

[0045] "Parts by mass" refers to the basic unit of measurement for expressing the mass ratio of multiple components. 1 part can represent any unit mass, such as 1g or 2.689g. If we say that the mass of component A is a parts and the mass of component B is b parts, it means the ratio of the mass of component A to the mass of component B is a:b. Alternatively, it means that the mass of component A is aK and the mass of component B is bK (K is an arbitrary number, indicating a multiple factor). It should not be misunderstood that, unlike the mass parts, the sum of the mass of all components is not limited to 100 parts.

[0046] "And / or" is used to indicate that one or both of the stated situations may occur, for example, A and / or B includes (A and B) and (A or B).

[0047] The present application provides a lithium iron manganese phosphate positive electrode material, comprising: a core and a coating layer located on the outer surface of the core, the material forming the core comprises lithium iron manganese phosphate, the material forming the coating layer comprises a high-conductivity compound, the high-conductivity compound comprises manganese and a non-metallic element, and the non-metallic element comprises any one of B, S, P, Si, As, and Se.

[0048] The present application forms a coating layer containing a highly conductive compound on the outer surface of the lithium manganese iron phosphate, thereby improving the conductivity of the lithium manganese iron phosphate positive electrode material and also improving the problem of manganese dissolution.

[0049] Specifically, the highly conductive compound of the present application has good stability and conductivity, improves the stability of the manganese element in the positive electrode material, and the Mn element in the positive electrode material of the present application is not easy to disproportionate to form divalent and tetravalent manganese. Moreover, the Mn in the highly conductive compound will not affect the performance of the lithium iron manganese phosphate lattice, and the Mn in the highly conductive compound can also play a certain role in repairing the loss of manganese dissolution during the charge and discharge process, which is beneficial to improve the electrochemical properties of the positive electrode material. If other metals besides Mn are contained in the highly conductive compound, other metal ions may enter the lithium iron manganese phosphate lattice, resulting in a decrease in material performance.

[0050] According to an embodiment of the present application, the highly conductive compound includes MnB2, MnS, MnP, MnSi, MnAs, and MnSe.

[0051] According to an embodiment of the present application, the proportion of the highly conductive compound in the lithium iron manganese phosphate positive electrode material is 0.05-0.5wt%; if the proportion of the highly conductive compound in the lithium iron manganese phosphate positive electrode material is too low, the improvement in manganese dissolution is small. Since the highly conductive compound itself does not have electrochemical activity, if the proportion of the highly conductive compound in the lithium iron manganese phosphate positive electrode material is too high, the polarization phenomenon generated by the battery during the charging and discharging process will be aggravated, resulting in a decrease in the battery voltage platform and rate performance.

[0052] For example, the proportion of the highly conductive compound in the lithium manganese iron phosphate positive electrode material can be 0.05wt%, 0.1wt%, 0.14wt%, 0.15wt%, 0.17wt%, 0.2wt%, 0.3wt%, 0.4wt%, 0.5wt% or any value between 0.05-0.5wt%.

[0053] And / or, the coating layer also includes carbon, and the carbon in the coating layer accounts for 1.5-2.5wt% in the lithium iron manganese phosphate positive electrode material; thereby, the positive electrode material can have both excellent electrical conductivity and high energy density. If the proportion of carbon in the coating layer in the lithium iron manganese phosphate positive electrode material is too low, the electrical conductivity of the positive electrode material will be poor. If the proportion of carbon in the coating layer in the lithium iron manganese phosphate positive electrode material is too high, the compaction density of the positive electrode material will be low, affecting the energy density of the battery.

[0054] For example, the proportion of carbon in the coating layer in the lithium manganese iron phosphate positive electrode material can be 1.5wt%, 1.6wt%, 1.7wt%, 1.8wt%, 1.9wt%, 2.0wt%, 2.1wt%, 2.2wt%, 2.3wt%, 2.4wt%, 2.5wt% or any value between 1.5-2.5wt%.

[0055] And / or, the coating layer has a thickness of 20-60 nm.

[0056] For example, the thickness of the coating layer may be 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, or any value between 20-60 nm.

[0057] According to an embodiment of the present application, the molar amount of manganese in the lithium manganese iron phosphate accounts for more than 60% of the sum of the molar amounts of manganese and iron;

[0058] And / or, the material forming the inner core includes carbon, and the carbon in the inner core accounts for 0.1-0.5 wt % of the inner core.

[0059] For example, the proportion of carbon in the core may be 0.1 wt%, 0.2 wt%, 0.3 wt%, 0.4 wt%, 0.5 wt% or any value between 0.1-0.5 wt%.

[0060] The present application also provides a method for preparing the lithium manganese iron phosphate positive electrode material as described above, comprising:

[0061] Mixing a lithium source, a first manganese source, an iron source, a phosphorus source, a first reducing carbon source and water, and sequentially performing a first spray drying and a first sintering process to obtain a core material;

[0062] The core material, the second reducing carbon source, the non-metallic element, the second manganese source and water are mixed, and a second spray drying and a second sintering process are performed in sequence to obtain a lithium manganese iron phosphate positive electrode material;

[0063] Wherein, the non-metallic element includes any one of B, S, P, Si, As, and Se.

[0064] According to an embodiment of the present application, the lithium source includes a lithium salt or a hydrate of a lithium salt, and the lithium salt includes at least one of lithium carbonate, lithium phosphate, lithium dihydrogen phosphate, and lithium hydroxide;

[0065] And / or, the first manganese source includes at least one of trimanganese tetroxide, manganese dioxide, dimanganese trioxide, and manganese carbonate;

[0066] And / or, the iron source includes at least one of ferric phosphate, ferric oxalate, ferric oxide, and ferrosoferric oxide;

[0067] And / or, the phosphorus source includes at least one of lithium dihydrogen phosphate, iron phosphate, ammonium dihydrogen phosphate, and phosphoric acid;

[0068] and / or, the molar ratio of lithium in the lithium source to manganese in the first manganese source, iron in the iron source, and phosphorus in the phosphorus source is 1.05:(0.50-0.90):(0.10-0.50):(1.00-1.03);

[0069] For example, the molar ratio of lithium in the lithium source to manganese in the first manganese source, iron in the iron source, and phosphorus in the phosphorus source can be any value between 1.05:0.50:0.10:1.00, 1.05:0.65:0.35:1.02, 1.05:0.60:0.40:1.02, 1.05:0.70:0.30:1.02, 1.05:0.90:0.50:1.03 or 1.05:(0.50-0.90):(0.10-0.50):(1.00-1.03).

[0070] And / or, the first reducing carbon source includes glucose; by adding the first reducing carbon source, the trivalent and / or tetravalent manganese ions in the first manganese source can be reduced to divalent, and the trivalent iron ions in the iron source can be reduced to divalent, which is conducive to the formation of lithium iron manganese phosphate crystal phase.

[0071] And / or, the content of the first reducing carbon source satisfies at least one of the following conditions: the ratio of the molar amount of the carbon element in the first reducing carbon source to the sum of the molar amounts of the trivalent metal elements in the first manganese source and the iron source is (1.02-1.1):4, and the ratio of the molar amount of the carbon element in the first reducing carbon source to the molar amount of the tetravalent manganese element in the first manganese source is (1.02-1.1):2;

[0072] And / or, before the first spray drying, the method further comprises a step of first grinding, and the D50 of the material after the first grinding is 0.18-0.22 μm;

[0073] And / or, the first sintering is performed under the protection of an inert gas, the temperature of the first sintering is 660-790° C., and the time of the first sintering is 8-14 hours.

[0074] For example, the first sintering temperature may be 660°C, 680°C, 700°C, 720°C, 750°C, 790°C or any value between 660-790°C.

[0075] The first sintering time may be 8 h, 9 h, 10 h, 11 h, 12 h, 13 h, 14 h or any value between 8 and 14 h.

[0076] According to an embodiment of the present application, the second reducing carbon source includes at least one of citric acid, ascorbic acid, tartaric acid, and gluconic acid; the above substances have strong reducing properties and acidity in aqueous solution, which can avoid oxidation reactions of non-metallic elements and is conducive to the formation of highly conductive compounds. If a carbon source with weak or no reducing properties is used, it is easy to cause oxidation of non-metallic elements during grinding, which is not conducive to the synthesis of highly conductive compounds. Moreover, the addition of the second reducing carbon source can also form a coating containing carbon on the outer surface of the lithium iron manganese phosphate core.

[0077] And / or, the second manganese source includes at least one of manganese acetate, manganese citrate, manganese oxalate, and manganese tartrate. The second manganese source of the present application does not contain any other elements except C, H, O, and Mn. The second manganese source can react to generate H2O and CO2, and other metal or non-metal impurities will not be introduced into the lattice or coating during the sintering process to affect the conductive properties. Moreover, the second manganese source has a high solubility in the solution, and the soluble second manganese salt can react more evenly with the non-metallic element in the liquid phase, which is conducive to forming a uniform coating.

[0078] According to an embodiment of the present application, the mass ratio of the core material to the second reducing carbon source is (17-20): 1. When the contents of the core material and the second reducing carbon source meet the above conditions, the positive electrode material can have both a higher energy density and a higher conductivity. If the content of the second reducing carbon source is too low, the conductivity of the positive electrode material will be reduced. If the content of the second reducing carbon source is too high, the energy density of the positive electrode material will be reduced due to the high content of inactive substances.

[0079] For example, the mass ratio of the core material to the second reducing carbon source can be 17:1, 18:1, 19:1, 20:1 or any value between (17-20):1.

[0080] According to an embodiment of the present application, the molar ratio of the non-metallic element to the manganese in the second manganese source is (1-2):1;

[0081] For example, the molar ratio of the non-metallic element to the manganese in the second manganese source can be 1:1, 2:1 or any value between (1-2):1.

[0082] And / or, the non-metallic element accounts for 0.015%-0.30% of the mass of the core material;

[0083] For example, the non-metallic element accounts for 0.015%, 0.02%, 0.025%, 0.03%, 0.037%, 0.04%, 0.048%, 0.049%, 0.05%, 0.055%, 0.06%, 0.1%, 0.20%, 0.25%, 0.30% or any value between 0.015% and 0.30% of the mass of the core material.

[0084] And / or, before the second spray drying, the method further comprises a step of performing a second grinding, and the D50 of the material after the second grinding is 0.20-0.40 μm. The particle size of the core material after the first sintering is relatively large, and the core material is a secondary particle agglomerate formed by the agglomeration of primary particles. The second grinding can disperse the primary particles, which is helpful to form a uniform coating layer on the surface of the primary particles; and the second grinding can also reduce the particle size of the non-metallic element, which is conducive to the reaction of the non-metallic element with the Mn element in the second manganese source to form a highly conductive compound.

[0085] If the particle size of the material after the second grinding is too small, the energy efficiency is higher. If the particle size of the material after the second grinding is too large, the activity of the non-metallic element is poor, which will lead to incomplete reaction, which is not conducive to the formation of highly conductive compounds, and it is easy to produce impurities, reduce the purity of the product, and thus affect the performance of the positive electrode material.

[0086] According to an embodiment of the present application, after the core material, the second reducing carbon source, the non-metallic element, the second manganese source, and water are mixed, the method further comprises the step of adjusting the pH of the slurry to 4.0-6.0; if the acidity of the slurry is too strong, the core material will be dissolved. If the alkalinity of the slurry is too strong, it is not conducive to the formation of a highly conductive compound.

[0087] Furthermore, the second reducing carbon source and lithium dihydrogen phosphate (phosphorus source) are both acidic, and the pH of the slurry can be maintained in the range of 4.0-6.0 by adjusting the addition amount of the second reducing carbon source and / or lithium dihydrogen phosphate (phosphorus source).

[0088] For example, the pH of the slurry may be adjusted to 4.0, 5.0, 6.0, or any value between 4.0 and 6.0.

[0089] And / or, the second sintering is carried out under the protection of an inert gas, and the temperature of the second sintering is 550-610°C; at the above sintering temperature, it is beneficial for the positive electrode material to have both high structural stability and high conductivity. If the temperature of the second sintering is too low, it is not conducive to the graphitization of carbon, which will cause the conductivity of the positive electrode material to weaken; at the same time, the reaction to form a highly conductive compound will be incomplete. If the temperature of the second sintering is too high, the manganese in the second manganese source is easily doped in the lattice of lithium manganese iron phosphate (LMFP), which is not conducive to the stability of the structure of the positive electrode material; at the same time, manganese and non-metallic elements are easy to form non-stoichiometric compounds, which will cause the conductivity of the positive electrode material to deteriorate.

[0090] For example, the second sintering temperature may be 550°C, 560°C, 570°C, 580°C, 590°C, 600°C, 610°C or any value between 550-610°C.

[0091] The second sintering time is 4-8h.

[0092] For example, the second sintering time may be 4 h, 5 h, 6 h, 7 h, 8 h or any value between 4 and 8 h.

[0093] The present application also provides a lithium-ion battery, which includes the lithium iron manganese phosphate positive electrode material described above or includes the lithium iron manganese phosphate positive electrode material prepared by the preparation method of the lithium iron manganese phosphate positive electrode material described above.

[0094] The embodiments of the present application will be described in detail below in conjunction with specific examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If specific conditions are not specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0095] 1. Preparation of lithium manganese iron phosphate positive electrode material

[0096] Example 1

[0097] Embodiment 1 provides a lithium manganese iron phosphate positive electrode material, and the preparation method thereof comprises:

[0098] (1) Weigh Li2CO3, MnO2, Fe2O3, LiH2PO4, and glucose. The contents of Li2CO3, MnO2, Fe2O3, and LiH2PO4 satisfy the molar ratio of Li, Mn, Fe, and P of 1.05:0.65:0.35:1.02, the ratio of the molar amount of carbon in glucose to the molar amount of trivalent iron in Fe2O3 is 1.05:4, and the ratio of the molar amount of carbon in glucose to the molar amount of MnO2 is 1.05:2.

[0099] Water is taken in an amount such that the solid content of the slurry after mixing Li2CO3, MnO2, Fe2O3, LiH2PO4, glucose and water is 40%.

[0100] Li2CO3, MnO2, Fe2O3, LiH2PO4, glucose and water were mixed in a stirring tank, ground in a sand mill to a D50 of 0.20 μm and then spray dried. The dried powder was sintered once under N2 conditions at a temperature of 700°C for 10 hours to obtain a core material.

[0101] The core material was tested using a carbon-sulfur analyzer, and the result showed that the carbon in the core material accounted for 0.15wt% of the core material mass.

[0102] (2) The core material, citric acid, elemental P, manganese citrate and pure water are mixed once. During the mixing, the mass ratio of the core material to the citric acid is controlled at 18:1, the elemental P accounts for 0.055% of the mass of the core material, the molar ratio of elemental P to manganese in manganese citrate is 1:1, the pH of the slurry is adjusted to 4.6, N2 is introduced into the stirring tank, the D50 is ground to 0.32 μm in a sand mill, and then spray-dried. The dried powder is secondary sintered under N2 conditions, the secondary sintering temperature is 570°C, and the secondary sintering time is 6 hours. After the secondary sintering is completed, it is crushed to obtain a lithium manganese iron phosphate positive electrode material.

[0103] The SEM image of the lithium manganese iron phosphate positive electrode material prepared in Example 1 is as follows Figure 1 As shown by Figure 1 It can be seen that the lithium manganese iron phosphate positive electrode material prepared in Example 1 is composed of primary particles with smooth surfaces.

[0104] The TEM image of the lithium manganese iron phosphate positive electrode material prepared in Example 1 is as follows Figure 2 As shown by Figure 2 It can be seen that the lithium manganese iron phosphate positive electrode material has an inner core and a coating layer covering the outer surface of the inner core, and the thickness of the coating layer is 40 nm.

[0105] The lithium iron manganese phosphate positive electrode material was tested using a carbon-sulfur analyzer, and it was found that the carbon in the coating layer accounted for 2.00wt% in the lithium iron manganese phosphate positive electrode material;

[0106] The lithium manganese iron phosphate positive electrode material was tested using an ICP inductively coupled plasma emission spectrometer, and the result showed that the generated MnP accounted for 0.15 wt % in the lithium manganese iron phosphate positive electrode material.

[0107] Example 2

[0108] Embodiment 2 provides a lithium manganese iron phosphate positive electrode material, and the preparation method thereof comprises:

[0109] (1) Weigh Li2CO3, Mn3O4, FePO4, LiH2PO4, and glucose. The contents of Li2CO3, Mn3O4, FePO4, and LiH2PO4 satisfy the molar ratio of Li, Mn, Fe, and P of 1.05:0.60:0.40:1.02, and the ratio of the molar amount of carbon in glucose to the sum of the molar amounts of trivalent metal elements in Mn3O4 and FePO4 is 1.06:4.

[0110] Water is taken in an amount such that the solid content of the slurry after mixing Li2CO3, Mn3O4, FePO4, LiH2PO4, glucose and water is 40%.

[0111] Li2CO3, Mn3O4, FePO4, LiH2PO4, glucose and water were mixed in a stirring tank, ground in a sand mill to a D50 of 0.20 μm and then spray dried. The dried powder was sintered once under N2 conditions at a temperature of 700°C for 10 hours to obtain a core material.

[0112] The core material was tested using a carbon-sulfur analyzer, and the result showed that the carbon in the core material accounted for 0.20wt% of the core material mass.

[0113] (2) The core material, ascorbic acid, elemental sulfur, manganese acetate and pure water are mixed once. During the mixing, the mass ratio of the core material to ascorbic acid is controlled at 20:1, the elemental sulfur accounts for 0.037% of the mass of the core material, the molar ratio of elemental sulfur to manganese in manganese acetate is 1:1, the pH of the slurry is adjusted to 5.0, N2 is introduced into the stirring tank, the D50 is ground to 0.35 μm in a sand mill, and then spray-dried. The dried powder is secondary sintered under N2 conditions, the secondary sintering temperature is 550°C, and the secondary sintering time is 6 hours. After the secondary sintering is completed, it is crushed to obtain a lithium manganese iron phosphate positive electrode material.

[0114] The lithium manganese iron phosphate positive electrode material prepared in Example 2 comprises an inner core and a coating layer covering the outer surface of the inner core, and the thickness of the coating layer is 30 nm.

[0115] The lithium iron manganese phosphate positive electrode material was tested using a carbon-sulfur analyzer, and the result showed that the carbon in the coating layer accounted for 1.80 wt % of the lithium iron manganese phosphate positive electrode material.

[0116] The lithium manganese iron phosphate positive electrode material was tested using an ICP inductively coupled plasma emission spectrometer, and the result showed that the generated MnS accounted for 0.10 wt % in the lithium manganese iron phosphate positive electrode material.

[0117] Example 3

[0118] Embodiment 3 provides a lithium manganese iron phosphate positive electrode material, and the preparation method thereof comprises:

[0119] (1) Weigh LiOH·H2O, Mn2O3, FeC2O4·2H2O, 85% H3PO4, and glucose. The contents of LiOH·H2O, Mn2O3, FeC2O4·2H2O, and 85% H3PO4 satisfy the molar ratio of Li, Mn, Fe, and P of 1.05:0.60:0.40:1.02, and the ratio of the molar amount of carbon in glucose to the molar amount of trivalent manganese in Mn2O3 is 1.08:4.

[0120] Water was measured so that the solid content of the slurry after mixing LiOH·H2O, Mn2O3, FeC2O4·2H2O, 85% concentration of H3PO4, glucose and water was 40%.

[0121] LiOH·H2O, Mn2O3, FeC2O4·2H2O, 85% concentration of H3PO4, glucose and water are mixed in a stirring tank, ground to D50 of 0.20 μm in a sand mill and then spray-dried. The dried powder is sintered once under N2 conditions at a temperature of 700°C and a sintering time of 10 hours to obtain a core material.

[0122] The core material was tested using a carbon-sulfur analyzer, and the result showed that the carbon in the core material accounted for 0.12 wt % of the core material mass.

[0123] (2) The core material, tartaric acid, elemental Si, manganese tartrate and pure water are mixed once. During the mixing, the mass ratio of the core material to citric acid is controlled at 17:1, the elemental Si accounts for 0.048% of the mass of the core material, the molar ratio of elemental Si to manganese in manganese tartrate is 1:1, the pH of the slurry is adjusted to 4.8, N2 is introduced into the stirring tank, the D50 is ground to 0.33 μm in a sand mill, and then spray-dried. The dried powder is secondary sintered under N2 conditions, the secondary sintering temperature is 610°C, and the secondary sintering time is 6 hours. After the secondary sintering is completed, it is crushed to obtain a lithium manganese iron phosphate positive electrode material.

[0124] The lithium manganese iron phosphate positive electrode material prepared in Example 3 comprises an inner core and a coating layer covering the outer surface of the inner core, and the thickness of the coating layer is 50 nm.

[0125] The lithium iron manganese phosphate positive electrode material was tested using a carbon-sulfur analyzer, and the result showed that the carbon in the coating layer accounted for 1.85wt% of the lithium iron manganese phosphate positive electrode material.

[0126] The lithium manganese iron phosphate positive electrode material was tested using an ICP inductively coupled plasma emission spectrometer, and the result showed that the generated MnSi accounted for 0.14wt% in the lithium manganese iron phosphate positive electrode material.

[0127] Example 4

[0128] Embodiment 4 provides a lithium manganese iron phosphate positive electrode material, and the preparation method thereof comprises:

[0129] (1) Weigh Li3PO4, MnCO3, Fe2O3, NH4H2PO4, and glucose. The contents of Li3PO4, MnCO3, Fe2O3, and NH4H2PO4 satisfy the molar ratio of Li, Mn, Fe, and P elements of 1.05:0.70:0.30:1.02, and the ratio of the molar amount of carbon element in glucose to the molar amount of trivalent iron element in Fe2O3 is 1.08:4.

[0130] Water is taken in an amount such that the solid content of the slurry after mixing Li3PO4, MnCO3, Fe2O3, NH4H2PO4, glucose and water is 40%.

[0131] Li3PO4, MnCO3, Fe2O3, NH4H2PO4, glucose and water were mixed in a stirring tank, ground in a sand mill to D50 of 0.20 μm and then spray dried. The dried powder was sintered once under N2 conditions at a temperature of 700°C for 10 hours to obtain a core material.

[0132] The core material was tested using a carbon-sulfur analyzer, and the result showed that the carbon in the core material accounted for 0.18 wt % of the core material mass.

[0133] (2) The core material, ascorbic acid, elemental B, manganese tartrate and pure water are mixed once. During the mixing, the mass ratio of the core material to ascorbic acid is controlled at 20:1, the elemental B accounts for 0.049% of the mass of the core material, the molar ratio of elemental B to manganese in manganese tartrate is 2:1, the pH of the slurry is adjusted to 5.2, N2 is introduced into the stirring tank, D50 is ground to 0.36 μm in a sand mill, and then spray-dried. The dried powder is secondary sintered under N2 conditions, the secondary sintering temperature is 580°C, and the secondary sintering time is 6 hours. After the secondary sintering is completed, it is crushed to obtain a lithium manganese iron phosphate positive electrode material.

[0134] The lithium manganese iron phosphate positive electrode material prepared in Example 4 comprises an inner core and a coating layer covering the outer surface of the inner core, and the thickness of the coating layer is 50 nm.

[0135] The lithium iron manganese phosphate positive electrode material was tested using a carbon-sulfur analyzer, and the result showed that the carbon in the coating layer accounted for 1.80 wt % of the lithium iron manganese phosphate positive electrode material.

[0136] The lithium manganese iron phosphate positive electrode material was tested using an ICP inductively coupled plasma emission spectrometer, and the result showed that the generated MnB2 accounted for 0.17wt% in the lithium manganese iron phosphate positive electrode material.

[0137] Comparative Example 1

[0138] The lithium manganese iron phosphate positive electrode material was prepared by referring to the method of Example 1. The other steps were the same as those of Example 1, except that manganese citrate and elemental P were not added in step (2) of Comparative Example 1.

[0139] Comparative Example 2

[0140] The lithium manganese iron phosphate positive electrode material was prepared by referring to the method of Example 1. The other steps were the same as those of Example 1, except that in step (2) of Comparative Example 2, only the core material, citric acid, manganese citrate and pure water were added.

[0141] Comparative Example 3

[0142] The lithium iron manganese phosphate positive electrode material was prepared by referring to the method of Example 1. The other steps were the same as those of Example 1, except that: in Comparative Example 3, step (2) was omitted, and the core material prepared in Example 1 was directly used as the lithium iron manganese phosphate positive electrode material.

[0143] Figure 3 This is a TEM image of the lithium manganese iron phosphate positive electrode material prepared in Comparative Example 3. Figure 3It can be seen that the outer surface of the product prepared in Comparative Example 3 has no coating layer.

[0144] 2. Performance Test

[0145] 1. Manganese dissolution test: Weigh 0.5 g of the lithium manganese iron phosphate positive electrode material prepared in the embodiment and the comparative example respectively and add them to a beaker, add 100 mL of 0.01 mol / L dilute hydrochloric acid to the beaker and stir on a magnetic stirrer for 30 min, remove the beaker and place it in a 25°C constant temperature water bath for 2 h, extract the filtrate with a vacuum filtration device and pour it into a volumetric flask to test the dissolved Mn ion content by ICP.

[0146] 2. Test of the proportion of high conductive compounds: Weigh 0.5g of the core material of the embodiment and the comparative example and the finished product (lithium manganese iron phosphate positive electrode material) respectively and add them to a beaker, add 20mL of 12mol / L dilute hydrochloric acid to the beaker and heat it on a hot plate. After dissolving, dilute and fix the volume, use ICP to test the content of non-metallic ions and Mn. The weight of the high conductive compound is obtained by subtracting the content of the core material (Mn, P or S, Si, B) from the finished product (Mn, P or S, Si, B). The ratio of the weight of the high conductive compound to the weight of the finished product is the proportion of the high conductive compound in the positive electrode material.

[0147] 3. Weigh 1.00 g of the lithium manganese iron phosphate positive electrode material prepared in the embodiment and the comparative example respectively and add it into the material cavity of the powder resistance testing instrument, and test the powder resistivity under a pressure of 8 MPa according to the process requirements.

[0148] 4. Capacity and cycle test: The lithium iron manganese phosphate positive electrode materials prepared in the embodiment and the comparative example are respectively used to prepare button batteries and conduct electrochemical performance tests. The specific steps include: the lithium iron manganese phosphate positive electrode material, the conductive agent cnt and the binder PVDF are uniformly mixed in NMP at a ratio of 90:5:5, and then coated on aluminum foil and placed in a vacuum drying oven for drying. After drying, the battery is assembled in an argon glove box, and pressed into a positive electrode sheet by a tablet press. The negative electrode is a metal lithium sheet, the electrolyte is 1M LiPF6-EC:DMC (volume ratio 1:1), and a polypropylene porous membrane is used as a diaphragm. The parameter conditions selected for testing the electrochemical performance are: the test voltage range is 2.5-4.3V, and 1C charge and discharge and cycle to 80% of the capacity is used as the cutoff condition.

[0149] The performance test results of the lithium manganese iron phosphate positive electrode materials prepared in the examples and comparative examples are shown in Table 1 below.

[0150] Table 1 Performance test results of lithium manganese iron phosphate positive electrode materials prepared in Examples and Comparative Examples

[0151]

[0152] It can be seen from Table 1 that the manganese dissolution rate in Example 1-4 is significantly lower than that in Comparative Example 1-3, and the cycle performance of Example 1-4 is significantly better than that of Comparative Example 1-3.

[0153] Compared with Comparative Examples 1-3, the positive electrode materials of Examples 1-4 have both lower manganese dissolution and lower resistivity. This is because the Mn element in Examples 1-4 can form a stable and highly conductive compound coating layer, which reduces the resistivity of the material while inhibiting the dissolution of manganese in lithium iron manganese phosphate, and can also repair the dissolution of Mn in the surface lattice of lithium iron manganese phosphate during the cycle, thereby significantly improving the cycle performance of the material.

[0154] In comparative example 2, manganese citrate was added in step (2), but the cycle performance of the positive electrode material was poor, and the resistance and Mn dissolution of the positive electrode material were high. This was because Mn did not form a compound with high conductivity and stability with other elements.

[0155] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.

[0156] In addition, those skilled in the art will appreciate that, although some embodiments herein include certain features included in other embodiments but not other features, the combination of features of different embodiments is meant to be within the scope of the present application and form different embodiments. For example, in the above claims, any one of the claimed embodiments may be used in any combination. The information disclosed in this background technology section is intended only to deepen the understanding of the overall background technology of the present application and should not be regarded as an admission or in any form of implication that the information constitutes prior art known to those skilled in the art.

Claims

1. A lithium manganese iron phosphate positive electrode material, characterized in that: include: An inner core and a coating layer located on the outer surface of the inner core, the material forming the inner core includes lithium manganese iron phosphate, the material forming the coating layer includes a high-conductivity compound, the high-conductivity compound includes manganese and a non-metallic element, and the non-metallic element includes any one of B, S, P, Si, As, and Se.

2. The lithium iron manganese phosphate positive electrode material according to claim 1, characterized in that: The high-conductivity compound accounts for 0.05-0.5wt% in the lithium iron manganese phosphate positive electrode material; And / or, the coating layer further includes carbon, and the carbon in the coating layer accounts for 1.5-2.5wt% of the lithium manganese iron phosphate positive electrode material; And / or, the coating layer has a thickness of 20-60 nm.

3. The lithium iron manganese phosphate positive electrode material according to claim 1 or 2, characterized in that: The molar amount of manganese in the lithium manganese iron phosphate accounts for more than 60% of the sum of the molar amounts of manganese and iron; And / or, the material forming the inner core includes carbon, and the carbon in the inner core accounts for 0.1-0.5 wt % of the inner core.

4. A method for preparing the lithium manganese iron phosphate positive electrode material according to any one of claims 1 to 3, characterized in that: include: A lithium source, a first manganese source, an iron source, a phosphorus source, a first reducing carbon source and water are mixed, and first spray drying and first sintering are performed in sequence to obtain a core material; The core material, the second reducing carbon source, the non-metallic element, the second manganese source and water are mixed, and a second spray drying and a second sintering process are performed in sequence to obtain a lithium manganese iron phosphate positive electrode material; Wherein, the non-metallic element includes any one of B, S, P, Si, As, and Se.

5. The method for preparing the lithium iron manganese phosphate positive electrode material according to claim 4, characterized in that: The lithium source includes a lithium salt or a hydrate of a lithium salt, and the lithium salt includes at least one of lithium carbonate, lithium phosphate, lithium dihydrogen phosphate, and lithium hydroxide; And / or, the first manganese source includes at least one of trimanganese tetroxide, manganese dioxide, dimanganese trioxide, and manganese carbonate; And / or, the iron source includes at least one of ferric phosphate, ferric oxalate, ferric oxide, and ferrosoferric oxide; And / or, the phosphorus source includes at least one of lithium dihydrogen phosphate, iron phosphate, ammonium dihydrogen phosphate, and phosphoric acid; and / or, the molar ratio of lithium in the lithium source to manganese in the first manganese source, iron in the iron source, and phosphorus in the phosphorus source is 1.05:(0.50-0.90):(0.10-0.50):(1.00-1.03); and / or, the first reducing carbon source comprises glucose; And / or, the content of the first reducing carbon source satisfies at least one of the following conditions: the ratio of the molar amount of the carbon element in the first reducing carbon source to the sum of the molar amounts of the trivalent metal elements in the first manganese source and the iron source is (1.02-1.1):4, and the ratio of the molar amount of the carbon element in the first reducing carbon source to the molar amount of the tetravalent manganese element in the first manganese source is (1.02-1.1):2; And / or, before the first spray drying, the method further comprises a step of first grinding, and the D50 of the material after the first grinding is 0.18-0.22 μm; And / or, the first sintering is performed under the protection of an inert gas, the temperature of the first sintering is 660-790° C., and the time of the first sintering is 8-14 hours.

6. The method for preparing the lithium iron manganese phosphate positive electrode material according to claim 4, characterized in that: The second reducing carbon source includes at least one of citric acid, ascorbic acid, tartaric acid, and gluconic acid; And / or, the second manganese source includes at least one of manganese acetate, manganese citrate, manganese oxalate, and manganese tartrate.

7. The method for preparing lithium iron manganese phosphate positive electrode material according to claim 6, characterized in that: The mass ratio of the core material to the second reducing carbon source is (17-20):

1.

8. The method for preparing lithium manganese iron phosphate positive electrode material according to claim 6, characterized in that: The molar ratio of the non-metallic element to the manganese in the second manganese source is (1-2):1; And / or, the non-metallic element accounts for 0.015%-0.30% of the mass of the core material; And / or, before the second spray drying, the method further comprises a second grinding step, and the D50 of the material after the second grinding is 0.20-0.40 μm.

9. The method for preparing the lithium manganese iron phosphate positive electrode material according to any one of claims 4 to 8, characterized in that: After mixing the core material, the second reducing carbon source, the non-metallic element, the second manganese source, and water, the method further comprises the step of adjusting the pH of the slurry to 4.0-6.0; And / or, the second sintering is performed under the protection of an inert gas, the temperature of the second sintering is 550-610° C., and the time of the second sintering is 4-8 hours.

10. A lithium ion battery, characterized in that: The lithium-ion battery comprises the lithium iron manganese phosphate positive electrode material according to any one of claims 1 to 3 or comprises the lithium iron manganese phosphate positive electrode material prepared by the method for preparing the lithium iron manganese phosphate positive electrode material according to any one of claims 4 to 9.